Benign Perivascular Epithelioid Cell Tumor of the Mesentery Misdiagnosed as a Uterine Fibroid: A Case Report and Review of Literature - Al-Nahhas, Omar; Haris, Aysha Simran; Raad, Yousif Basim; Alkheder, Khaled Alaboud; Miyata, Kenichi (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Perivascular epithelioid cell tumor (PEComa) is a type of mesenchymal tumor composed of histologically and immunohistochemically distinctive perivascular epithelioid cells. Benign mesenteric PEComa is a rare entity as there has been only one case reported so far. We are presenting a case of benign mesenteric PEComa in a 30-year-old female that presented with abdominal pain and was diagnosed by microscopic morphological examination and immunohistochemical staining. The aim of this case report is to make health-care professionals aware of the diagnostic criteria in similar presentations, treatment modalities offered for this patient, and others reported over the years for malignant as well as benign PEComas and also shedding the light on a new presentation and diagnosis. CASE REPORT: We reported a case of a 30-year-old female who presented with abdominal pain radiating to the back and rectum. After a thorough physical examination which was unremarkable, a CT scan was done which showed a mesenteric mass. This mass was then resected and sent for histopathology which revealed a PEComa. We report the history, clinical findings, laboratory reports, and gross imaging of a 30-year-old female who presented to our clinic and was diagnosed with a very rare benign mesenteric PEComa. CONCLUSION: PEComa is a rare tumor, and as PEComas arising from the mesentery being one of the rarer kinds with only 10 cases reported and this case being the 11th, out of those ten cases, only two of them were found to be benign which makes the case we are reporting the second benign mesenteric PEComa reported in English Literature.